Gastric cancer, gastritis and the role of H. pylori - Axon, Anthony (Henry Stewart Talks, 2011)
Helicobacter pylori (Hp) and gastric cancer, Natural history of Hp gastritis, Hp as an essential risk factor, Mechanisms of carcinogenesis, Why the variation in cancer incidence?